Design, controlled synthesis, and properties of 2D CeO2/NiO heterostructure assemblies. Issue 48 (29th November 2017) - Song, Caixia; Zhao, Jian; Li, Honghao; Luo, Shizhong; Tang, Yubao; Wang, Debao
Abstract : Synthetic protocols to generate well-integrated frameworks of known composition are important for the rational design of advanced materials. Abstract : Synthetic protocols to generate well-integrated frameworks of known composition are important for the rational design of advanced materials. 3D CeO2 /NiO hierarchical assemblies were designed and constructed with 2D CeO2 /NiO heterostructures as building blocks consisting of NiO nanosheets wrapped with CeO2 ultrathin nanosheets on the surfaces. The growth process of the 2D CeO2 /NiO heterostructure nanosheets and the 3D assemblies was described based on a domain-matching growth process. The CeO2 /NiO assemblies exhibited superior catalytic properties for CO oxidation. A model of the structure–property relationships based on surface and interface structures is discussed.